Fenomena Alih Kode dan Campur Kode dalam Interaksi Mahasiswa di Pekalongan - Eska Rojwa Fauziah; Nadifa Nurul Aina; Dita Ayu Purwanti; Nazwa Mirda Maisari; Wirayudha Pramana Bhakti (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study analyzes the sociolinguistic phenomena of code-switching and code-mixing in the academic context of students in Pekalongan, Central Java. As a region with diverse backgrounds dominated by the Pekalongan dialect (Ngapak Javanese), interactions between students create space for complex language dynamics. This study aims to identify variations, roles, and factors that cause code-switching and code-mixing in student interactions. The method applied is descriptive qualitative with data collection through inactive participant observation, recording, and in-depth interviews at various universities in Pekalongan. Data analysis is carried out through the steps of data reduction, data presentation, and verification using triangulation techniques. The results show that the application of language codes is divided into two categories: an internal category that includes Indonesian and regional languages (Javanese), and an external category that includes foreign languages (English or Arabic). Code-mixing can be found at the word, phrase, and clause levels. The main factors that drive this phenomenon include participants, conversation themes, situational circumstances, and the purpose of communication in building solidarity among group members (ingroup).  The Pekalongan dialect plays a crucial role as a means of communication to build closeness and demonstrate local identity, amidst the need to use formal language on campus. This research concludes that code-switching and code-mixing are not merely linguistic phenomena, but also ways in which students adapt socially to balance their cultural identity with academic demands.